Tricuspid valve endocarditis with septic pulmonary emboli in a drug addict - Weymann, Alexander; Schmack, Bastian; Rosendal, Christian; Karck, Matthias; Szabó, Gábor (Annals of thoracic and cardiovascular surgery, 2012)
Japan's largest platform for academic e-journals: J-STAGE is a full text database for reviewed academic papers published by Japanese societies